2007
DOI: 10.1007/s10725-007-9225-8
|View full text |Cite
|
Sign up to set email alerts
|

Possible correlation between high temperature-induced floret sterility and endogenous levels of IAA, GAs and ABA in rice (Oryza sativa L.)

Abstract: In order to explore the possible physiological mechanism of high temperature induced sterility in rice, we examined the floret sterility and endogenous plant growth regulator contents in pollens of two hybrid rice cultivars Shanyou63 and Teyou559 that are tolerant and susceptible to high temperature, respectively. Indexes of floret sterility, pollen activity, and variation of endogenous indole-3-acetic acid (IAA), gibberellic acids (GAs), abscisic acid (ABA), free proline and soluble proteins in anthers were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(87 citation statements)
references
References 9 publications
5
81
0
1
Order By: Relevance
“…Protein content as well as activities of GOT and GPT of grains increased in all the cultivars with both hormones (Tables 1 and 3). Increase in soluble protein in pollen of rice under high temperature stress was observed by Tang et al (2008) which contributes to maintain cell structure and function under abiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Protein content as well as activities of GOT and GPT of grains increased in all the cultivars with both hormones (Tables 1 and 3). Increase in soluble protein in pollen of rice under high temperature stress was observed by Tang et al (2008) which contributes to maintain cell structure and function under abiotic stresses.…”
Section: Resultsmentioning
confidence: 99%
“…For ABA, the relationship is less clear. In rice florets exposed to reoccurring heat stress for 5 d, ABA concentrations were higher than under control conditions (Tang et al, 2008). Although it has been shown that ABA contributes to heat acclimation of vegetative organs (Larkindale and Huang 2005), this has not been shown for reproductive tissue.…”
Section: Distinguishing Acclimation From Injurymentioning
confidence: 90%
“…Pro acts as a compatible solute in osmoprotection and accumulates in response to different abiotic stresses (Krasensky and Jonak, 2012). Pro is a key factor for pollen viability (Lansac et al, 1996), and in several species, levels decrease in pollen under high temperature regimes that disturb pollen development (Mutters et al, 1989;Tang et al, 2008). Interestingly, the expression of Pro transporter 1 mRNA was reduced under these conditions.…”
Section: Other Types Of Heat Injurymentioning
confidence: 99%
“…Compared to the sensitive genotype, the tolerant retained significantly higher levels of free proline and GAs and a lower level of ABA, along with higher pollen vigour and pollen germination rate even after prolonged high temperature treatment. This study also suggests a possible correlation between pollen viability/floret sterility and high temperature-caused changes in endogenous ABA levels (Tang et al, 2008). Unlike droughtsensitive wheat varieties, drought-tolerant wheat accumulates less ABA, which correlates with lower ABA biosynthesis and higher ABA catabolic gene expression.…”
Section: Introductionmentioning
confidence: 55%